2018
DOI: 10.22159/ajpcr.2018.v11i11.29006
|View full text |Cite
|
Sign up to set email alerts
|

Normal Fasting Blood Sugar Levels and Medication Adherence Improve the Quality of Life of Type 2 Diabetes Mellitus Patients in Primary Health Facilities

Abstract: Objective: The aim of the overall study was to determine the quality of life (QOL) and the factors that influence it in patients with diabetes mellitus (DM) in primary health care (PHC) Jetis 1, Bantul.Methods: This cross-sectional study was conducted on 153 DM patients in PHC Jetis I, Bantul. Respondents were recruited by inclusion and exclusion criteria. Primary data on exposure to cigarette smoke, adherence with physical activity, perception of disease, and QOL are collected through interviews. Data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Diabetes mellitus is more common in women [14]. However, research by Khan et al (2011) which states that men are more susceptible to diabetes mellitus than women, this occurs in South Asia and China [15]. Table 3 shows that there is no significant difference between INF-γ and glucose levels with age under 60 years and above 60 years, with p value greater than 0.05 (p > 0.05).…”
Section: Ifn-and Glucose Levels In Dm Patients and Related Factorsmentioning
confidence: 90%
“…Diabetes mellitus is more common in women [14]. However, research by Khan et al (2011) which states that men are more susceptible to diabetes mellitus than women, this occurs in South Asia and China [15]. Table 3 shows that there is no significant difference between INF-γ and glucose levels with age under 60 years and above 60 years, with p value greater than 0.05 (p > 0.05).…”
Section: Ifn-and Glucose Levels In Dm Patients and Related Factorsmentioning
confidence: 90%
“…The number of samples was determined using the Lemeshow formula. The standard deviation from type I error = 1.96, the standard deviation from type II error is 0.84, with a minimum odds ratio that is considered significant is 2.8 [21]. The proportion of exposure is0.5, and the dependent variable rate is 0.5.…”
Section: Subject and Research Materialsmentioning
confidence: 99%
“…to 0.36 (taken from previous research data) and rate of a case with exposure was 0.63 then the results of the sample size calculation using the open epi application are 96. 8 The inclusion criteria were (i) patients with type 2 diabetes mellitus without or with comorbidities treated at the outpatient clinic of Jetis I PHC, Bantul; (ii) patients, both male and female, aged 18 -85 years; (iii) receiving one or more antidiabetic drugs, both oral and insulin; and (iv) willing to participate in this study by signing informed consent. The exclusion criteria for the subjects of this study were (i) pregnant type 2 D.M.…”
Section: Original Articlementioning
confidence: 99%
“…7 A study using the pill count method at the urban Community Health Center reported that 54.35% of diabetes mellitus patients were not adherent to treatment. 8 Research in primary health care in Indonesia shows a relationship between non-adherence to taking medication with hypercreatininemia in patients with metabolic syndrome. 8 One of the complications of diabetes mellitus is a kidney disease characterized by above regular creatine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation